Lösungsverfahren für das many-to-one Matching Problem - Herzog, Elvira

Cooperative Transfer Price Negotiations under Incomplete Information - Brangewitz, Sonja; Haake, Claus-Jochen
In this paper, we analyze a model in which two divisions negotiate over an intrafirm transfer price for an intermediate product. Formally, we consider bargaining problems under incomplete information, since the upstream division’s (seller's) costs and downstream division's (buyer's) revenues are supposed to be private information. Assuming two possible types for buyer and seller each, we first establish that the bargaining problem is regular, regardless whether incentive and/or efficiency constraints are imposed. This allows us to apply the generalized Nash bargaining solution to determine transfer payments and transfer probabilities. Furthermore, we derive general properties of this solution for the transfer pricing problem and compare the model developed here with the existing literature for negotiated transfer pricing under incomplete information. In particular, we focus on the models presented in Wagenhofer (1994).
Keywords: Transfer Pricing; Negotiation; Generalized Nash Bargaining Solution; Incomplete Information

How many attackers can selfish defenders catch? - Mavronicolas, Marios; Monien, Burkhard; Papadopoulou Lesta, Vicky (Discrete Applied Mathematics)
In a distributed system with attacks and defenses, both attackers and defenders are self-interested entities. We assume a reward-sharing scheme among interdependent defenders; each defender wishes to (locally) maximize her own total fair share to the attackers extinguished due to her involvement (and possibly due to those of others). What is the maximum amount of protection achievable by a number of such defenders against a number of attackers while the system is in a Nash equilibrium? As a measure of system protection, we adopt the Defense-Ratio (Mavronicolas et al., 2008)[20], which provides the expected (inverse) proportion of attackers caught by the defenders. In a Defense-Optimal Nash equilibrium, the Defense-Ratio matches a simple lower bound.We discover that the existence of Defense-Optimal Nash equilibria depends in a subtle way on how the number of defenders compares to two natural graph-theoretic thresholds we identify. In this vein, we obtain, through a combinatorial analysis of Nash equilibria, a collection of trade-off results:• When the number of defenders is either sufficiently small or sufficiently large, Defense-Optimal Nash equilibria may exist. The corresponding decision problem is computationally tractable for a large number of defenders; the problem becomes NPNP-complete for a small number of defenders and the intractability is inherited from a previously unconsidered combinatorial problem in Fractional Graph Theory.• Perhaps paradoxically, there is a middle range of values for the number of defenders where Defense-Optimal Nash equilibria do not exist.

Effizienzsteigerung durch gewichtete Produktbewertungen - Reineke, Max

Dynamic One-to-One Matching: Theory and a Job Market Application - Stroh-Maraun, Nadja

Der Einfluss adaptierter Erwartungen in dynamischen Cournot Oligopolen - Kornhoff, Tobias

Auktionen im Beschaffungsmanagement - Eine spieltheoretische Analyse - Meckenstock, Kevin

Asymmetric Nash bargaining solutions and competitive payoffs - Brangewitz, Sonja; Gamp, Jan-Philip (Economics Letters)
We establish a link between cooperative and competitive behavior. For every possible vector of weights of an asymmetric Nash bargaining solution there exists a market that has this asymmetric Nash bargaining solution as its unique competitive payoff vector.

Negotiating Transfer Prices - Haake, Claus-Jochen; Martini, Jan Thomas (Group Decision and Negotiation)

On the institutional design of burden sharing when financing external border enforcement in the EU - Haake, Claus-Jochen; Krieger, Tim; Minter, Steffen (International Economics and Economic Policy)

Stability of Coalitional Equilibria within Repeated Tax Competition - Brangewitz, Sonja; Brockhoff, Sarah
This paper analyzes the stability of capital tax harmonization agreements in a stylized model where countries have formed coalitions which set a common tax rate in order to avoid the inefficient fully non-cooperative Nash equilibrium. In particular, for a given coalition structure we study to what extend the stability of tax agreements is affected by the coalitions that have formed. In our set-up, countries are symmetric, but coalitions can be of arbitrary size. We analyze stability by means of a repeated game setting employing simple trigger strategies and we allow a sub-coalition to deviate from the coalitional equilibrium. For a given form of punishment we are able to rank the stability of different coalition structures as long as the size of the largest coalition does not change. Our main results are: (1) singleton regions have the largest incentives to deviate, (2) the stability of cooperation depends on the degree of cooperative behavior ex-ante.

Revenue-maximizing Order of Sale in Sequential Auctions - Drücker, Julian

Penny Auctions: Design und Strategisches Verhalten - Celik, Aydin

Minimizing Expectation Plus Variance - Mavronicolas, Marios; Monien, Burkhard (Proceedings of the 5th International Symposium on Algorithmic Game Theory (SAGT))
We consider strategic games in which each player seeks a mixed strategy to minimize her cost evaluated by a concave valuation V (mapping probability distributions to reals); such valuations are used to model risk. In contrast to games with expectation-optimizer players where mixed equilibria always exist [15, 16], a mixed equilibrium for such games, called a V -equilibrium, may fail to exist, even though pure equilibria (if any) transfer over. What is the impact of such valuations on the existence, structure and complexity of mixed equilibria? We address this fundamental question for a particular concave valuation: expectation plus variance, denoted as RA, which stands for risk-averse; so, variance enters as a measure of risk and it is used as an additive adjustment to expectation. We obtain the following results about RA-equilibria:- A collection of general structural properties of RA-equilibria connecting to (i) E-equilibria and Var-equilibria, which correspond to the expectation and variance valuations E and Var, respectively, and to (ii) other weaker or incomparable equilibrium properties.- A second collection of (i) existence, (ii) equivalence and separation (with respect to E-equilibria), and (iii) characterization results for RA-equilibria in the new class of player-specific scheduling games. Using examples, we provide the first demonstration that going from E to RA may as well create new mixed (RA-)equilibria.- A purification technique to transform a player-specific scheduling game on identical links into a player-specific scheduling game so that all non-pure RA-equilibria are eliminated while new pure equilibria cannot be created; so, a particular game on two identical links yields one with no RA-equilibrium. As a by-product, the first-completeness result for the computation of RA-equilibria follows.

Methoden zur Bestimmung von innerbetrieblichen Verrechnungspreisen - Mammadov, Fuad

Managerial Delegation and Capacity Choices: An Analysis of the Cournot-Nash Equilibrium - Löwen, Xenia

Learning by Trading in Infinite Horizon Strategic Market Games with Default - Brangewitz, Sonja
We study the consequences of dropping the perfect competition assumption in a standard infinite horizon model with infinitely-lived traders and real collateralized assets, together with one additional ingredient: information among players is asymmetric and monitoring is incomplete. The key insight is that trading assets is not only a way to hedge oneself against uncertainty and to smooth consumption across time: It also enables learning information. Conversely, defaulting now becomes strategic: Certain players may manipulate prices so as to provoke a default in order to prevent their opponents from learning. We focus on learning equilibria, at the end of which no player has incorrect beliefs — not because those players with heterogeneous beliefs were eliminated from the market (although default is possible at equilibrium) but because they have taken time to update their prior belief. We prove a partial Folk theorem à la Wiseman (2011) of the following form: For any function that maps each state of the world to a sequence of feasible and strongly individually rational allocations, and for any degree of precision, there is a perfect Bayesian equilibrium in which patient players learn the realized state with this degree of precision and achieve a payoff close to the one specified for each state.

Effiziente Paketbildung in mehrdimensionalen Verhandlungsproblemen - Kluczniok, Sven

Alternative Berechnung der Machtindizes: Banzhaf und Shapley-Shubik Index - Dawirs, Friederike

Coalitional and Strategic Market Games - Brangewitz, Sonja